The Role of Needs Analysis in English for Specific Purposes - Gusti Astika (TEFLIN Journal: A publication on the teaching and learning of English, 1999)
This article discusses the role of needs analysis in ESP. Teaching ESP should not be considered as a different kind of teaching the language but rather as an approach as it is also based on the commonly held belief of teaching language for communicative purposes. The problems that ESP teachers have are similar to those of teachers of English for general purposes although there are a some additional problems that may lie beyond methods and pedagogy especially those related to non-linguistic matters. Students needs are discussed from different angles and the theoritical basis of needs analysis is derived from the ideas of communicative competence proposed by Hymes (1972) and Canale and Swain (1980). Different approaches to needs analysis and its importance are also discussed. Finally, a model of framework for needs analysis as a basis for syllabus design is presented.